Investigation of the Effective Reinforcement Modulus of Carbon Nanotubes in an Epoxy Matrix - Martone, Alfonso; Faiella, Gabriella; Antonucci, Vincenza; Giordano, Michele; Zarrelli, Mauro (IntechOpen, 2011)
None